KAJIAN PENGARUH PENGAMBILAN AIRTANAH LOKASI SEKITAR RUMAHSAKIT PENDIDIKAN UNIVERSITAS DIPONEGORO TERHADAP SUMBER AIR MASYARAKAT DENGKEKSARI, KECAMATAN TEMBALANG, KOTA SEMARANG - Tyas Putri Maharani (Geological Engineering E-Journal, 2014)
Pendidikan Universitas Diponegoro Hospital is located on the Campus  of Diponegoro University, Tembalang, Semarang is the hospital that was built for the ministry of health, this condition is certainly to need water to meet their daily.This needs are from groundwater through water sources that are owned. Pendidikan Universitas Diponegoro Hospital to make 3 deepwell with 80-120 metres deep. In addition the Dengkeksari society located in the north of hospital, use spring to provide their daily in water. They live under the clif or rock in front of the hospital. The springs flow hole volcanic brecia layer, then water is used by the society to provide their daily need in water.It needs to do an observation to know aquifer condition used by hospital and society of Dengkeksari. This observation uses schlumberger geoelectric method. So the condition under surface in observation location is detectable. So the location of aquifer used by hospital and the society is known.Based on the result of log geolistrik can be seen that the resource is in aquifer layer primer and deepwell of the hospital are in aquifer layer second, so there is no negatif effect of using the deepwell with the condition of the resource used by dengkeksari because of difference aquifer..